ANALYSIS OF POTENTIAL DEVELOPMENT OF INLAND FISHERY IN THE DISTRICT OF EAST KOLAKA - Lukman Yunus; Muhammad Ramli; Yusnaeni Yusnaeni; Muhammad Aswar Limi (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
ABSTRACTThe existence of Fishery Potential resources in the county of East Kolaka is a comparatif advantage that will be valuable if it is supported by analysis of potency about inland fishery development according to the area characteristics. The objectives of this research are to analyze the strategies and potencies of inland fishery in East Kolaka. The research location was focused on the center of inland fishery development in all districts areas. The method of data analyses were consist of qualitative, quantitative and spatial analyses. From the result of this research, it can be concluded that: (a) The district of Ladongi and Mowewe are considerably accepted as the center of fish breeding, (b) the center of fish maturation in the development of inland fishery is divided into five subclusters, (ponds, rawa, bendungan/waduk, river and persawahan, (c) the center of inland fish pocessing consists of two subclusters which are cullinary and fishery product diversivication.Keywords: potency, development, inland fishery.